EFEKTIFITAS TEHNIK HIPNOTIK LIMA JARI TERHADAP TINGKAT ANSIETAS PASIEN YANG DIRAWAT DI RUMAH SAKIT HUSADA JAKARTA - Setyaningsih, Tri (Jurnal Kesehatan Holistic, 2017)
Hospitalized is an unpleasant experience for many people and even many who experience anxiety. This study aims to determine the effect of hypnotic five fingers to decline patient's anxiety in Husada Hospital. This research uses a method of quasi-experimental pre-post test with out control group with sample of participants is 79 people. The results of this study indicate that there is no difference in the characteristics of age, there is a significant difference in patients' blood pressure before and after the five fingers hypnotic intervention (p <0.05). There is significant difference in differences in anxiety cognitive ability before and after the intervention (p <0.05). There is significant difference between anxiety and motor function before and after the intervention, there is a significant difference between anxiety and communication skills before and after the intervention (p <0.05). The test results showed five fingers hypnotic able to reduce the anxiety of patients in Hospital p = 0.00 (p <0.05). Hypnotic techniques five fingers can be used by the nurses to reduce anxiety of patients admitted to hospital.